Study of the PTGS suppressor activity of V2 protein from geminivirus Beet curly top virus - Pérez-Luna, Ana Isabel; Rodríguez-Negrete, Edgar; Castillo, D.; Morilla, Gabriel; Wang, Liping; Lozano-Durán, Rosa; Rodríguez-Bejarano, Eduardo (My University, 2017)
Suppression of gene silencing is a key mechanism for the success of viral infection in plants. DNA viruses from the Geminiviridae family encode several proteins that suppress post- and transcriptional gene silencing (PTGS/TGS). In Begomovirus V2 has been shown to be the strongest PTGS suppressor in transient assays. Beet curly top virus (BCTV), the model species for the Curtovirus genus, is able to infect the widest range of plants among geminiviruses. In this genus, only C2 protein has been described to inhibit PTGS and TGS. Objective: Our main goal is to test the PTGS suppressor activity of BCTV V2 and to study further its gene-silencing suppression mechanism. Material and methods: To determine whether BCTV V2 is also a gene silencing suppressor we carried out transient expression assays in Nicotiana benthamiana wild-type or the 16c GFP-expressing line: plant leaves were agroinfiltrated with binary constructs to express GFP (35S:GFP) and V2. Visual detection of GFP fluorescence was confirmed by western blot. Relative levels of the GFP-specific siRNAs were determined by northern blot. We also expressed the V2 ORF from a Potato virus X-derived vector in N. benthamiana plants. As an approach to identify a genetic target of V2 in the antiviral silencing pathway, we carried out a complementation analysis of BCTV-∆V2 in a series of Arabidopsis thaliana mutants deficient in specific components of this pathway involved in DNA virus siRNA production and amplification (DCL2, DCL3, DCL4, RDR6 and RDR2). Arabidopsis plants were infected by agroinoculation and the amount of viral DNA was measured by real-time qPCR. To gain more insight into the gene silencing suppression mechanism of V2, we generated Arabidopsis plants overexpressing the viral protein. Wild-type (Col-0) plants, as well as, plants containing the SUC-SUL hairpin or the AMPLICON (AMP) constructs were transformed with the same V2 expression cassette used for the gene silencing assays. Results: Like its begomoviral counterpart, BCTV V2 is a potent PTGS suppressor and produces an HR-like response in N. benthamiana plants when expressed from PVX. The molecular and genetic analysis of transgenic plants expressing V2 indicates that, as the begomoviral V2, BCTV V2 inhibits the RDR6/SGS3-dependent silencing pathway. Finally, infection assays in Arabidopsis mutants confirm the importance of the RDR6/SGS3 pathway in defence against curtoviruses, and reveal an additional RDR6/SGS3-independent gene-silencing suppression mechanism of V2. Conclusions: BCTV V2, as begomovirus V2 protein, suppresses PTGS by impairing the RDR6/SGS3 pathway. Keywords: Geminivirus, BCTV V2, RNA-silencing suppressor.
Keywords: Enfermedades por virus; Geminivirus; Silencing suppressor; V2